1992
DOI: 10.1002/iroh.19920770206
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Associations in the Middle Niger‐Sokoto Basin (Nigeria: West Africa)

Abstract: The species richness of the crustacean zooplankton (Cladocera and Copepoda) and Rotifera in the Middle Niger-Sokoto Basin is characterised from 35 1 samples collected from 109 localities. 26(4) Cladocera, 18(8) Copepoda and 38(8) Rotifera are recorded. Figures in brackets indicate first records of species for Nigeria. Zooplancton associations of the Middle Niger are compared with one of its major tributaries, River Sokoto, and seven of its minor tributaries using similarity indices of S~rensen and Pearsons Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…The observed dominance by copepods in the reservoirs was not surprising. However, this study only reported high abundance and dominance of copepods and cladocerans, a finding different from documented works on other African water bodies, including Lake Cubhu (Martin & Cyrus ), Ogun and Ona rivers (Akin‐Oriola ) and Niger‐Sokoto River (Jeje & Fernando ), which also reported a high abundance of rotifers, in addition to copepods and cladocerans.…”
Section: Discussioncontrasting
confidence: 99%
“…The observed dominance by copepods in the reservoirs was not surprising. However, this study only reported high abundance and dominance of copepods and cladocerans, a finding different from documented works on other African water bodies, including Lake Cubhu (Martin & Cyrus ), Ogun and Ona rivers (Akin‐Oriola ) and Niger‐Sokoto River (Jeje & Fernando ), which also reported a high abundance of rotifers, in addition to copepods and cladocerans.…”
Section: Discussioncontrasting
confidence: 99%
“…Kirk & Gilbert (1990) have noted this type of scenario in a tropical reservoir. The low genera abundance of cladocerans and copepods have also been documented in other water bodies like Lake Cubhu, South Africa (Martin & Cyrus 1994), Ogun and Ona rivers (Akin-Oriola 2003) and Niger-Sokoto River (Jeje & Fernando 1992). The predominance of Daphnia among the cladocerans could have arisen due to its large bodied size which enables it to graze on large quantities and diverse forms of phytoplankton.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, Korinek (1984) surveyed c. 50 localities (in all, c. 100 samples) in the Upper Zaire Valley, Central Africa, and recorded 53 species of Cladocera here, only three of which were Daphnia. Not only are the tropics therefore probably richer on a unit areal basis than the non-tropics, but studies like Jeje & Fernando (1992), wherein a remarkably low number of crustaceans was reported from a large area and numerous samples in Nigeria, indicate that their material was not exhaustively studied.…”
Section: Lake-per-lake Comparisonsmentioning
confidence: 99%